Model-Driven Approach of Virtual Interactive Environments for Enhanced User Experience - Héctor Cardona-Reyes; Jaime Muñoz-Arteaga; Andres Mitre-Ortiz; Klinge Orlando Villalba-Condori (Applied Sciences, 2021)
The video game and entertainment industry has been growing in recent years, particularly those related to Virtual Reality (VR). Therefore, video game creators are looking for ways to offer and improve realism in their applications in order to improve user satisfaction. In this sense, it is of great importance to have strategies to evaluate and improve the gaming experience in a group of people, without considering the fact that users have different preferences and, coupled with this, also seeks to achieve satisfaction in each user. In this work, we present a model to improve the user experience in a personal way through reinforcement learning (RL). Unlike other approaches, the proposed model adjusts parameters of the virtual environment in real-time based on user preferences, rather than physiological data or performance. The model design is based on the Model-Driven Architecture (MDA) approach and consists of three main phases: analysis phase, design phase, and implementation phase. As results, a simulation experiment is presented that shows the transitions between undesired satisfaction states to desired satisfaction states, considering an approach in a personal way.